ABOUT LEXEMES RELATED TO THE TERMS “GANJ” AND “GAVKHAR” IN THE NAVOI EPIC “SADDI ISKANDARI” (Scientific journal of the Fergana State University, 2024)
This article talks about the Persian words used by the poet in Alisher Navoi's work "Saddi Iskandari". The etymological characteristics of the Persian words "ganj" and "gavhar" in the work, their lexical meanings, based on comments in Persian-Tajik dictionaries, comparison with comments given in other sources, lexical meanings of Persian words in the annotated dictionary of Navoi's works scientific opinions are presented. The explanation of the Persian words based on the lexemes "Ganj" and "gavhar" was defined as the main goal of the article. The lexical and semantic meanings of the Persian words presented in the article are explained, and it is revealed through examples that personal nouns are formed on the basis of them.